Telomere Length and Emotional and Behavioral Problems in Children from the Prospective Birth Cohort INfancia y Medio Ambiente (INMA) Study - Irene Campos-Sánchez; Eva María Navarrete-Muñoz; Josep Xavier Barber-Valles; Dries S. Martens; Isolina Riaño-Galán; Amaia Irizar; Sabrina Llop; Mónica Guxens; Cristina Rodríguez-Dehli; Izaro Babarro; Manuel Lozano; Martine Vrijheid; et al. (Children)
Background/Objectives: This study aimed to examine the association between leukocyte telomere length (TL) measured at ages 4 and 8 and emotional and behavioral problems at age 8. We also explored whether changes in leukocyte TL between ages 4 and 8 were associated with outcomes. Methods: Data were obtained from a population-based birth cohort and included 647 children with TL at age 4 and emotional and behavioral assessments at age 8, 673 with TL and outcomes at age 8, and 315 with TL measured at both ages. TL was determined using quantitative PCR on blood samples and converted into z-scores for analysis. Emotional and behavioral problems—including internalizing, externalizing, and total difficulties—were assessed using the Strengths and Difficulties Questionnaire. Regression models were conducted using zero-inflated and negative binomial, adjusting for sociodemographic and lifestyle covariates. Results: No statistically significant associations were observed between leukocyte TL at ages 4 or 8, or TL changes over this period, and emotional and behavioral outcomes at age 8. Conclusions: Although no significant associations were found, further longitudinal research is warranted to clarify the role of TL as a potential psychobiomarker of emotional and behavioral disorders in childhood.